Earth's Correlation Wavefield: Late Coda Correlation. Issue 7 (13th April 2018) - Phạm, Thanh‐Son; Tkalčić, Hrvoje; Sambridge, Malcolm; Kennett, Brian L. N.
Abstract: Cross correlation of seismograms provides new information on the Earth both through the exploitation of ambient noise and specific components of earthquake records. Here we cross‐correlate recordings of large earthquakes on a planetary scale and identify a range of hitherto unobserved seismic phases in Earth's correlation wavefield. We show that both arrivals with the timing expected for the regular seismic wavefield and previously unexplained phases are produced by interference between seismic paths having the same ray parameter but with only a subset of propagation legs in common. This insight explains the origin and generation mechanism of the features of Earth's correlation wavefield and opens up new ways of addressing issues in global seismology. Strong similarity between observed and synthesized correlation wavefields indicates that the Earth's radial structure is remarkably well constrained in the intermediate period range. Plain Language Summary: We investigate the nature of earthquake coda waveform cross correlations and provide an explanation for the origin of, what we term here, the Earth's correlation wavefield. This consists of numerous correlated signals some that appear similar to regular seismic phases and others not apparent in the conventional seismic wavefield. The nature of the correlation wavefield described here has far‐reaching implications for the field of seismology. In particular, we show that the correlated wavefield illuminates the Earth's interior in an entirely new and unexpected manner. With further method developments we expect this to lead to improved structural constraints on the Earth interior, especially in the poorly sampled regions such as the Earth's lowermost mantle and core. Key Points: Global cross correlation of earthquake coda reveals the Earth's correlation wavefield that consists of numerous correlated phases The similarity between the observed and synthesized correlation wavefields indicates that the Earth's radial structure is well constrained Correlated phases are explained by interference of a pair of seismic phases with the same ray parameter and a subset of legs in common